PENGARUH TERPAAN TIKTOK “SECRET RECIPE” TERHADAP MINAT BELI STARBUCKS PADA MAHASISWA DI INDONESIA (Studi Kasus Video “Secret Recipe” @Decxymalvin di TikTok) (E-Jurnal Medium, 2022)
TikTok is a social networking application that is known as a place to do business, creating interesting content from various categories and attracting new users continuously to increase the existence of the application itself. A Starbucks barista with the TikTok account @Decxymalvin is one of the content providers who uses social media to promote knowledge. @Decxymalvin posts some fascinating content, including the debut of "Secret Recipe," a secret recipe not found on the official Starbucks menu. The goal of this study is to see how @Decxymalvin's "Secret Recipe" video affects Starbucks' buying interest among Indonesian students. Dennis Mcquail's Stimulus Organism Response Theory was applied in this study. Frequency, Duration, and Intensity are three indicators used to determine exposure. Explorative Interest, Transactional Interest, Referential Interest, and Preferential Interest are markers of buying interest.The results of this study reveal that there is a relationship between the two variables, with a regression coefficient of 0.794 indicating a substantial relationship. The Rsquare value of 0.630 suggests that 63 percent of Indonesian students are interested in purchasing Starbucks, while the remaining 37 percent is impacted by variables outside of this survey. It does, however, have a major favorable impact. After viewing the video "Secret Recipe" by @Decxymalvin, students in Indonesia are interested in purchasing. The highest average score on the buying interest variable demonstrates this. This alone is sufficient to show a shift in buying interest. Keywords: Exposure, TikTok, Secret Recipe @Decxymalvin, Buying Interest, College Students